STRATEGI STARBUCKS CORPORATIONS DALAM MEMBAWA PENGARUH WAVES OF COFFEE CULTURE DI JEPANG TAHUN 2005 - Fijria Putri Hadane; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research exexplains about starbucks corporation strategy to bring the influence of waves of coffee culture in Japan. Starbucks is a Multinational Corporations (MNCs) of the United States which has 1,034 outlets across Japan. Starbucks entered Japan in 1995 and took a local Japanese company that is Sazaby Inc. in their efforts to enter the Japanese market and to determine the market appetite in Japan. Starbucks set up many stores in major urban centers in Japan as an attempt to facilitate a Starbucks in introducing its products to the people of Japan.This Research collects data from books, journal, and website which discusses the existence of starbucks in Japan. To analyze starbucks corporation strategy to bring the influence of waves of coffee culture in Japan, this research using competitive advantantage and using liberalism perspective. Starbucks chose Japan as her first Asian expansion region because they have same philosophy similarities between Japanese and American society are equally concerned with time.This research shows that starbucks managed to bring the influence of waves of coffee culture in Japan with evidence of the increasing number of similar businesses that appeared in Japan and has its own uniqueness. Japan is also the country with the world's coffee imports to meet domestic demand and currently many emerging businesses alike who come from outside Japan also followed Starbucks in the market expansion efforts.Keywords: Starbucks Corp, Waves of Coffee Culture, Competitive Advantages, Liberalism